Effect of internet-based guided self-help vs individual face-to-face treatment on full or subsyndromal binge eating disorder in overweight or obese patients: the INTERBED randomized clinical trial - Zwaan, Martina de; Friederich, Hans-Christoph (JAMA psychiatry, 2017)
Importance Although cognitive behavioral therapy (CBT) represents the criterion standard for treatment of binge eating disorder (BED), most individuals do not have access to this specialized treatment. Objective To evaluate the efficacy of internet-based guided self-help (GSH-I) compared with traditional, individual face-to-face CBT. Design, Setting, and Participants The Internet and Binge Eating Disorder (INTERBED) study is a prospective, multicenter, randomized, noninferiority clinical trial (treatment duration, 4 months; follow-ups, 6 months and 1.5 years). A volunteer sample of 178 adult outpatients with full or subsyndromal BED were recruited from 7 university-based outpatient clinics from August 1, 2010, through December 31, 2011; final follow-up assessment was in April 2014. Data analysis was performed from November 30, 2014, to May 27, 2015. Interventions Participants received 20 individual face-to-face CBT sessions of 50 minutes each or sequentially completed 11 internet modules and had weekly email contacts. Main Outcomes and Measures The primary outcome was the difference in the number of days with objective binge eating episodes (OBEs) during the previous 28 days between baseline and end of treatment. Secondary outcomes included OBEs at follow-ups, eating disorder and general psychopathologic findings, body mass index, and quality of life. Results A total of 586 patients were screened, 178 were randomized, and 169 had at least one postbaseline assessment and constituted the modified intention-to-treat analysis group (mean [SD] age, 43.2 [12.3] years; 148 [87.6%] female); the 1.5-year follow-up was available in 116 patients. The confirmatory analysis using the per-protocol sample (n = 153) failed to show noninferiority of GSH-I (adjusted effect, 1.47; 95% CI, −0.01 to 2.91;P = .05). Using the modified intention-to-treat sample, GSH-I was inferior to CBT in reducing OBE days at the end of treatment (adjusted effect, 1.63; 95% CI, 0.17-3.05;P = .03). Exploratory longitudinal analyses also showed the superiority of CBT over GSH-I by the 6-month (adjusted effect, 0.36; 95% CI, 0.23-0.55;P < .001) but not the 1.5-year follow-up (adjusted effect, 0.91; 95% CI, 0.54-1.50;P = .70). Reductions in eating disorder psychopathologic findings were significantly higher in the CBT group than in the GSH-I group at 6-month follow-up (adjusted effect, −0.4; 95% CI, −0.68 to −0.13;P = .005). No group differences were found for body mass index, general psychopathologic findings, and quality of life. Conclusions and Relevance Face-to-face CBT leads to quicker and greater reductions in the number of OBE days, abstinence rates, and eating disorder psychopathologic findings and may be a better initial treatment option than GSH-I. Internet-based guided self-help remains a viable, slower-acting, low-threshold treatment alternative compared with CBT for adults with BED. Trial Registration isrctn.org Identifier:ISRCTN40484777and germanctr.de Identifier:DRKS00000409